2019
DOI: 10.1002/ceat.201800386
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Adsorption Behavior of CO2, CH4, and N2 on Different Types of BETA Zeolites

Abstract: The adsorption equilibrium and kinetics of CO 2 , CH 4 , and N 2 on three types of BETA zeolites were investigated at different temperatures and a defined partial pressure range from dynamic breakthrough experiments. The adsorbed amount followed the decreasing order of CO 2 > CH 4 > N 2 for all studied materials. For the same ratio of SiO 2 /Al 2 O 3 , the Na-BETA-25 zeolite showed a higher uptake capacity than H-BETA-25, due to the presence of a Na + cationic center. Comparing the same H + compensation cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 73 publications
0
31
0
Order By: Relevance
“…Furthermore, the gas-solid interaction energy can be tuned by changing the metal cation, [6][7][8] cation concentration, [9][10][11] or the size or topology of the zeolite micropores. 12,13 The adsorption of CO 2 in alkali ion-exchanged zeolites has been extensively investigated experimentally and by computational methods. [6][7][8][9][10][11][12][13][14][15][16][17][18] It was found that the cation-CO 2 geometry is related to the nature of alkali cations on the Y zeolite, where the adsorption enthalpies show a decrease from Li + to Cs 7+ .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the gas-solid interaction energy can be tuned by changing the metal cation, [6][7][8] cation concentration, [9][10][11] or the size or topology of the zeolite micropores. 12,13 The adsorption of CO 2 in alkali ion-exchanged zeolites has been extensively investigated experimentally and by computational methods. [6][7][8][9][10][11][12][13][14][15][16][17][18] It was found that the cation-CO 2 geometry is related to the nature of alkali cations on the Y zeolite, where the adsorption enthalpies show a decrease from Li + to Cs 7+ .…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption of CO 2 on the newly developed adsorbents CMSW-S-800 and CMSW-800-S was assessed in the temperature range of 40-100°C by applying the CCD as a design mod-el to the experimental runs [31][32][33]. The experimental values of input variables and their coded values, and also the response surfaces for CMSW-800-S and CMSW-S-800 samples are listed in Tab The obtained experimental values were fitted with quadratic models to develop the general correlations for the uptake capacity and the breakthrough time of the specified samples.…”
Section: Central Composite Design Analysismentioning
confidence: 99%
“…In the last step, desorption process was performed by passing pure helium through the fixed bed. More details about the unit can be found elsewhere [4,10].…”
Section: Breakthrough Experiments (Screening Studies)mentioning
confidence: 99%
“…Currently, various classes of adsorbents including carbons based materials [4,7,8], zeolite molecular sieves [9,10], metal organic frameworks [11,12], meso-porous silicons [13,14] and other ones [15,16] have been extensively investigated for separation processes, energy conversion, and catalysis. Among different developed materials, activated carbons (ACs) are highly favorable adsorbents for CO 2 adsorption for several reasons [17].…”
Section: Introductionmentioning
confidence: 99%